G-quadruplexes Sequester Free Heme in Living Cells. Issue 12 (19th December 2019) - Gray, Lucas T.; Puig Lombardi, Emilia; Verga, Daniela; Nicolas, Alain; Teulade-Fichou, Marie-Paule; Londoño-Vallejo, Arturo; Maizels, Nancy
Summary: Heme is an essential cofactor for many enzymes, but free heme is toxic and its levels are tightly regulated. G-quadruplexes bind heme avidly in vitro, raising the possibility that they may sequester heme in vivo . If so, then treatment that displaces heme from quadruplexes is predicted to induce expression of genes involved in iron and heme homeostasis. Here we show that PhenDC3, a G-quadruplex ligand structurally unrelated to heme, displaces quadruplex-bound heme in vitro and alters transcription in cultured human cells, upregulating genes that support heme degradation and iron homeostasis, and most strikingly causing a 30-fold induction of heme oxidase 1, the key enzyme in heme degradation. We propose that G-quadruplexes sequester heme to protect cells from the pathophysiological consequences of free heme. Graphical Abstract: Highlights: Physiological evidence of the privileged partnership of G-quadruplexes and heme A role for G-quadruplexes in protecting cells from oxidative damage caused by heme A role for heme in regulating gene expression by binding non-B form nucleic acids Abstract : Gray, Puig Lombardi et al. unravel a role for G-quadruplexes in sequestering heme in living cells, thereby protecting cells from oxidative damage elicited by free heme, and using heme as a cofactor to support specialized function of some quadruplexes.